Control, Deception, and Communication: Evaluating the Deployment of a Location-Enhanced Messaging Service - Iachello, G.; Smith, I.; Consolvo, S.; Abowd, G.D.; Hughes, J.; Howard, J.; Potter, F.; Scott, James; Sohn, T.; Hightower, J.; LaMarca, A. (Proceedings of the Fifth International Conference on Ubiquitous Computing (UbiComp 2005), 2005)
We report on a two-week deployment of a peer-to-peer, mobile, location-enhanced messaging service. This study is specifically aimed at investigating the need for and effectiveness of automatic location disclosure mechanisms, the emerging strategies to achieve plausible deniability, and at understanding how place and activity are used to communicate plans, intentions and provide awareness. We outline the research that motivated this study, briefly describe the application we designed, and provide details of the evaluation process. The results show a lack of value of automatic messaging functions, confirm the need for supporting plausible deniability in communications, and highlight the prominent use of activity instead of place to indicate one’s location. Finally, we offer suggestions for the development of social mobile applications.